Ru Nanoparticles Supported on Oxygen‐Deficient 3DOM BiVO4: High‐Performance Catalysts for the Visible‐Light‐Driven Selective Oxidation of Benzyl Alcohol. Issue 24 (18th November 2019) - Zhang, Kunfeng; Liu, Yuxi; Deng, Jiguang; Jing, Lin; Pei, Wenbo; Han, Zhuo; Zhang, Xing; Dai, Hongxing
Abstract: Developing novel photocatalysts for green synthesis of important organic intermediates under mild conditions is of great significance in industry. In this work, we synthesized the oxygen‐deficient three‐dimensionally ordered macroporous (3DOM) BiVO4 ‐supported nanosized Ru ( x Ru/3DOM BiVO4, x =0.24–2.16 wt %) catalysts by the polymethyl methacrylate‐templating, ethylene glycol reduction, and post‐thermal treatment methods. Physicochemical properties of the materials were characterized using the various techniques, and their catalytic activities for the visible‐light‐driven selective oxidation of benzyl alcohol to benzaldehyde were measured. It is found that the Ru nanoparticles (NPs) with a size of 1.2–1.5 nm were uniformly dispersed on the surface of 3DOM BiVO4, which gave rise to a significant enhancement in photocatalytic activity. Benzyl alcohol conversion first went up and then dropped down with the rise in loading of Ru NPs. The 0.95Ru/3DOM BiVO4 −Ar‐300 sample was thermally treated in an Ar flow at 300 °C for 4 h showed the highest benzyl alcohol conversion (78 %) with a benzaldehyde selectivity of 100 % (benzaldehyde formation rate was 1380 μmol/(g h) after 6 h of illumination) and good photocatalytic stability. The high dispersion of Ru NPs and formation of oxygen vacancies in 3DOM BiVO4 improved separation and transfer efficiency of the photogenerated electrons/holes and increased the superoxide radical concentration. In addition, the possible mechanism of benzyl alcohol oxidation over 0.95Ru/3DOM BiVO4 −Ar‐300 was also discussed. The oxygen‐deficient 3DOM BiVO4 ‐supported Ru NPs have promising applications for selective oxidation of organics. Abstract : Photocatalysis : The 0.95Ru/3DOM BiVO4 −Ar‐300 photocatalysts are prepared by the ethylene glycol reduction and post‐thermal treatment methods. Excellent photocatalytic performance for the selective oxidation of benzyl alcohol to benzaldehyde over 0.95Ru/3DOM BiVO4 −Ar‐300 is associated with Ru loading on 3DOM BiVO4 and formation of oxygen vacancies in 3DOM BiVO4 that favors generation of highly active superoxide radicals and high separation efficiency of the photogenerated electrons and holes.